Transport services: destination management perspective - Becková, Helena; Nováková, Božena (Melandrium, 2018)
Transport belongs to essential services provided in tourism. Visitors need a whole range of services, but first of all transport services that enable them to reach the respective destination and to get back as well as to move about the destination. Transport represents one of the important factors that can influence visitors' decision-making concerning the choice of the destination. However, transport doesn't serve only for transfer of visitors. Transport itself can be an important tourist attraction. Transport issues solving is thus an important task for destination management. The paper deals with the problems of transport just from the destination management perspective. It examines theoretical background of the relation between transport and tourism and aims to map the role of transport in present destination management. The attention is paid to the situation in the Czech Republic, in its particular regions, by means of a surrey via questionnaire among existing destination management organizations. The results can be used for the improvement of destination management in the Czech Republic.
Dopravní služby: pohled destinačního managementu
Keywords: destination management; tourism; transport; destinační management; cestovní ruch; doprava